2019
DOI: 10.1371/journal.pone.0225893
|View full text |Cite
|
Sign up to set email alerts
|

Women with metabolic syndrome show similar health benefits from high-intensity interval training than men

Abstract: High-intensity interval training (HIIT), is effective to improve cardiorespiratory fitness (CRF) and metabolic syndrome (MetS) components in adults. However, it is unclear if CRF and MetS components respond similarly in men and women after HIIT. For 16 weeks, 63 women (53±7 years) and 56 men (55±8 years) with MetS underwent a three day/week HIIT program. Bodyweight and composition, VO2MAX, surrogate parameters of CRF (Ventilatory threshold (VT), oxygen uptake efficiency slope (OUES) and VE/VCO2 slope), maximal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 61 publications
1
6
0
1
Order By: Relevance
“…We also showed that exercise combined with KD significantly improved the Zmets compared to exercise alone. In line with our results, previous studies have shown that low carbohydrate diet (48) and a physical activity (49) interventions improve the most prevalent MetS components, especially MetS z-score (Zmets). Because the measures of interaction on the additive scale revealed that the combined effects of exercise and KD on Zmets were more than the sum of the individual effects, current results support their synergistic effect and importance for the control of metabolic syndrome conditions.…”
Section: Discussionsupporting
confidence: 92%
“…We also showed that exercise combined with KD significantly improved the Zmets compared to exercise alone. In line with our results, previous studies have shown that low carbohydrate diet (48) and a physical activity (49) interventions improve the most prevalent MetS components, especially MetS z-score (Zmets). Because the measures of interaction on the additive scale revealed that the combined effects of exercise and KD on Zmets were more than the sum of the individual effects, current results support their synergistic effect and importance for the control of metabolic syndrome conditions.…”
Section: Discussionsupporting
confidence: 92%
“…The major finding in the present study was the significantly greater improvement in the metabolic cardiovascular risk factors reported in the experimental group compared to the control group. This finding can be solely attributed to the HIIT, and it can be explained by several physiological adaptations/responses, as described by Serrablo-Torrejon et al [40], as follows: (a) HIIT-mediated reduction in waist circumference, an effect that was reported in metabolic syndrome by many studies [9][10][11][12][13][14][15][16][17][18]. The HIIT-induced decrease in WC can be related to reduced visceral or abdominal fatness owing to excess post-exercise oxygen consumption (EPOC) and increases in fat oxidation during recovery periods of HIIT [41].…”
Section: Discussionmentioning
confidence: 97%
“…In the last decade, a considerable number of studies have investigated the effectiveness of HIIT in metabolic syndrome [9][10][11][12][13][14][15][16][17][18][19]. These studies have shown that HIIT is an effective exercise strategy in metabolic syndrome management yielding significant improvements in waist circumference (WC) [9][10][11][12][13][14][15][16][17][18], serum triglycerides (TG) [10,19], systolic blood pressure (SBP) and diastolic blood pressure (DBP) [9][10][11][12][13][14][15][16][17][18], high-density lipoproteins (HDL) [9,19], blood glucose (BG) [10,11,15], and body weight and/or body mass index (BMI) [11,13,16,17]. Also, HIIT combined with dietary restriction has resulted in positive changes in the cardiometabolic profile in metabolic syndrome [20,21].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Além disso, estudos anteriores demonstraram resultados semelhantes em relação a perda de peso e melhora do condicionamento e resistência após a realização do HIIT em ratos Zucker (Maillard et al, 2019), crianças obesas (Liu, et al, 2019), mulheres com sobrepeso (Mirghani et al, 2019), e homens obesos (Smith-Ryan et al, 2015) o qual evidencia o benefício desse exercício, principalmente pelo fato de que a maioria das pessoas que praticam o HIIT, buscam pelo emagrecimento e melhora do condicionamento físico (Ito, 2019;Guio et al, 2019 (Adolfo et al, 2019).…”
Section: Discussionunclassified